G266(P) To Vaccinate or Not to Vaccinate. (24th May 2017) - Mehta, R
Abstract : Aim: Structured clinical question: Would giving live rota virus vaccine (I) in corrected term baby (P) with ileostomy make a difference to the stoma out put and the weight gain (O)? P: patient I: intervention C: Control/Comparator O: Outcome Methods: 28 week preterm infant who is 10 weeks old with corrected gestation of 38 weeks, has an ileostomy following necrotising enterocolitis at 6 weeks of age. Infant had poor weight gain and increase in the feeds lead to high stoma out put. Baby is due her first set of immunisations. Rota virus is contraindicated in confirmed anaphylactic reaction to a previous rotavirus vaccine or the component of vaccine, previous history intussusception, over 24 weeks of age, infants presenting for their first dose of Rotarix over 15 weeks of age, Severe Combined Immunodeficiency (SCID) disorder, malformation of GI tract that could predispose to intussusception, rare hereditary problems of fructose intolerance, glucose-galactose malabsorption or sucrose-isomaltose insufficiency. 1 Results: Literature search yielded case series by Tingay et al. As demonstrated by this retrospective study ileostomy losses were highly variable through the study period and did not emerge to be correlated with vaccination in most infants. Also the weight gain was maintained in all infants before and after vaccination. Limitations of the study: It was a small retrospective study with likely selection bias. 2 Conclusion: There are no further studies for babies who have undergone ileostomy and received rota virus vaccination. Further studies should be undertaken to establish safety of the rota virus immunisation in babies with ileostomy. Rota virus vaccination should not be dismissed but carefully considered in such infants. If decision is made to give the vaccine in infants with ileostomy, fluid and electrolyte balance should be carefully monitored and sodium intake should be optimised. References: https://www.gov.uk/government/uploads/system/uploads/attachment_data/file/457263/Green_Book_Chapter_27b_v3_0.pdf Early observations in the use of oral rotavirus vaccination in infants with functional short gut syndrome Alice YW Fang, David G Tingay,